Analisis Penggunaan Noni dan Nagaramo Dalam Kalimat Bahasa Jepang: Kajian Semantik - Putri Bintang Pratiwi Harahap; Dedi Sutedi; Susi Widianti (KIRYOKU, 2020)
This research is a  semantic study focusing on the use of keredemo and nagaromo in Japanese. The purpose of this study is to find out how keredemo and nagaramo are used in Japanese and also to find out the differences and similarities contained in keredemo and nagaramo in Japanese. keredemo and nagaramo are one of the learning materials at Bachelor degree. Based on the type of research (qualitative) and the topic raised by the author, descriptive analysis methods are considered appropriate to describe problem. Based on data analysis, it can be concluded that setsuzokujoshi keredomo and nagaramo have almost the same function. Keredomo and Nagaramo basically have the same meaning that is equally meaningful though / but. the meaning of setsuzokujoshi keredemo shows several functions, which are used for meaningful sentences that are unexpected, contrary to reality, comparison, expressing opinions, expressing feelings of disappointment, keredomo functions are almost the same as nagaramo. setsuzokujoshi nagaramo can also be used in meaningful sentences that are unexpected, contrary to reality, and express feelings of disappointment but the difference between nagaramo and keredemo is nagaramo is usually used to express the feelings of others, relatives or closest people, nagaramo also cannot be used to comparison, because nagaramo is not usually for equivalent compound sentences.